2018
DOI: 10.1111/hae.13480
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent F8 and F9 gene variants result from a founder effect in two large French haemophilia cohorts

Abstract: Introduction Haemophilia A (HA) and haemophilia B (HB) are X‐linked recessive diseases, caused by a large number of pathogenic variants in the F8 and F9 genes. With the exception of introns 22 and 1 inversions which are frequent in severe HA cases, about 2000 unique variants in F8 and 1000 in F9 have been described in databases and their recurrence remains limited. Aim and methods During routine analysis, we identified two recurrent missense variants, the F8 gene c.1244C>T, p.Ala415Val variant in 27 HA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Detailed polymerase chain reaction (PCR) conditions for each marker have been previously described. 6…”
Section: Haplotype Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed polymerase chain reaction (PCR) conditions for each marker have been previously described. 6…”
Section: Haplotype Analysismentioning
confidence: 99%
“…Several studies have reported a founder effect for other F8 variations found at a relatively high frequency in HA patients. [3][4][5][6][12][13][14][15] In these studies, the variations associated with a founder effect were found among a small number of selected patients and/or in a geographically isolated population. In contrast, herein, the DEL13T was found in a large number of apparently unrelated HA families from several areas of France.…”
Section: Essentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining two markers were extragenic; DF2 was located at the telomeric side of F8 , and DXS8061 was at the centromeric side. Detailed PCR conditions for each marker have been previously described 8,16 . The characteristics of each STR used in this study are listed in Table .…”
Section: Methodsmentioning
confidence: 99%